PENERAPAN PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING PADA PRODUK UMKM REMPEYEK MATAHARI KHAS BALI; STUDI KASUS USAHA RUMAHAN CRUSTY CRIPS - Wahyuni, Komang Tri; Maheswari, Putu Gittanirwana Adinda (STAI Denpasar Bali, 2024)
This research is a case study that aims to determine the method of calculating the cost of production based on full costing. The data used in this study are primary and secondary, with the research location at the UMKM Crusty Crips located on Jalan Nangka Utara, Denpasar. Crusty Crisp was established in 2020. This product is a Balinese rempeyek (peyek) in the shape of a sunflower madefrom natural ingredients and typical Indonesian spices. The data collection method used is to analyze the elements of production costs (manufacturing costs) such as direct raw material costs, direct labor and factory overhead costs, where the calculation of full costing includes elements of factory overhead costs, both fixed cost elements and variable cost elements.